The Constitutional concept of National security policy under the Constitution of the Republic of Iraq for the year 2005 - Ali, Sadiq; Attia, Ali (Journal of Legal Sciences, 2023)
The Constitution of the Republic of Iraq for the year 2005 dealt with the policy of national security as an exclusive competence of the federal authorities, and the policy of national security as one of the forms of general policies that the constitution enclosed in privacy when it was stipulated in particular, and this policy also attracted the attention of comparative constitutional examples, as it stipulated the formation of specialized constitutional councils to undertake The process of developing and implementing this policy, or forming specialized institutions for this matter, and according to the national security policy, the unity of policies in the state is ensured and directed towards achieving the requirements of Iraqi national security, through planning, coordination and evaluation of national interests, and accordingly directing the necessary resources to achieve them, because security has become in The development of its concept and the diversification of its fields required a unified policy that guarantees the unity of these efforts aimed at achieving it.